Association Between Functional Nucleotide Polymorphisms Up-regulating Transforming Growth Factor β1 Expression and Increased Tuberculosis Susceptibility. (16th September 2020) - Zhang, Su; Li, Guobao; Bi, Jing; Guo, Qinglong; Fu, Xiangdong; Wang, Wenfei; Liu, Shuyan; Xiao, Guohui; Ou, Min; Zhang, Juanjuan; He, Xing; Li, Fang; et al.
Abstract: Previous studies demonstrated that transforming growth factor (TGT) β1 plays an immunosuppressive role in clinical tuberculosis. However, the contribution of TGF-β1 gene polymorphisms to human tuberculosis susceptibility remains undetermined. In this study, we showed that single-nucleotide polymorphisms (SNPs) in TGF-β1 gene were associated with increased susceptibility to tuberculosis in the discovery cohort (1533 case patients and 1445 controls) and the validation cohort (832 case patients and 1084 controls), and 2 SNPs located in the promoter region (rs2317130 and rs4803457) are in strong linkage disequilibrium. The SNP rs2317130 was associated with the severity of tuberculosis. Further investigation demonstrated that rs2317130 CC genotype is associated with higher TGF-β1 and interleukin 17A production. The mechanistic study showed that rs2317130 C allele affected TGF-β1 promoter activity by regulating binding activity to nuclear extracts. These findings provide insights into the pathogenic role of TGF-β1 in human tuberculosis and reveal a function for the TGF-β1 promoter SNPs in regulating immune responses during Mycobacterium tuberculosis infection. Abstract : Functional single-nucleotide polymorphism of rs2317130 CC genotype, up-regulating Mycobacterium tuberculosis –specific transforming growth factor β1 and interleukin 17A expression, is associated with increased tuberculosis susceptibility.